Dealing with difference and dissensus within the church as organisation - Painter-Morland, M. (Verbum et ecclesia, 2001)
This paper wants to propose a way of dealing with the reality of difference within churches that allows for unity amidst diversity. It argues for the adoption of institutional frameworks that function as guiding and unifying forces without becoming repressing, totalising structures. The presence of dissensus and difference does not necessarily have to result in the fragmentation of churches. In fact, when harnessed effectively, difference and dissensus can become a valuable resource for renewal and realignment within churches. The paper develops a framework for dealing with diversity that binds people to the church as organisation in a way that respects their individual value-configurations and input. In the first place, it argues for a holistic view of the relationship between bodiliness, nature, technology, language, and truth statements. In the second place, it insists that confessional, spiritual and moral guidelines should neither be totalising structures that repress difference, nor oppositional differences that exclude commonality. In the third place, it argues that ongoing connectedness between individual members of the church is necessary. Individuals must see themselves as part of an everchanging, ever-evolving web of relations. Guidelines for dialogue within the church therefore become essential.